APLIKASI MOBILE ARSIP PRODI MENGGUNAKAN FRAMEWORK CORDOVA (STUDI KASUS : PRODI TEKNIK INFORMATIKA INSTITUT SHANTI BHUANA) - Nurcahyo, Azriel Christian; Firgia, Listra; Hammad, Rifqi (Universitas Janabadra, 2021)
The use of mobile-based applications has become a necessity for routine administration, especially for lecturers at the Shanti Bhuana Institute, Bengkayang, West Kalimantan. Twice weekly study program meetings, namely tuesday and friday, are an obligation so that lecturers can evaluate the performance with the head of the study program and the vice chancellor regarding the progress of each study program line such as research, community service, teaching and learning activities, even workshops. However, the briefing was limited to communication via whats app during the pandemic season making it difficult to recap the minutes during the briefing, especially as a report to the stakeholders.The NopTI application (Notulen Arsip Prodi TI) is presented to make it easier for lecturers to archive routine briefings based on mobile android. By using the cordova framework which is still rare in developing mobile applications and utilizing google drive as a storage medium, it will certainly reduce costs in terms of database storage. Applications are used more than 80% by IT lecturers, 60% use online briefings, 40% offline briefings and black box tested by several IT experts valid 100% fulfilled from the functions tested, and can be used on android 8.0 to 10.0 and a delay of 186.414 ms nice category to open apps.Keywords: administration, mobile, briefings, cordova..